PEMANFAATAN ECENG GONDOK SEBAGAI PUPUK ORGANIK UNTUK MENINGKATKAN EKONOMI MASYARAKAT DI DANAU TOBA SUMATERA UTARA - Abdurrozzaq Hasibuan; Nurul Hasanah, Rehuliana Ninta Br Sitepu, Shelly Shabina Putri Sinaga; Suhela Putri Nasution (CV. ADIBA AISHA AMIRA, 2023)
Water hyacinth is an aquatic weed whose life cycle is floating in waters or raising roots in mud in shallow waters. The purpose of this water hyacinth itself is to be able to minimize abandoned plant gardens on Lake Toba, so that water hyacinth in the area grows to be more useful, both for the environment and for society. This study uses literature studies, the object of this research is information systems and previous research related to the phenomena discussed, this aims to develop solutions and related problems. The results showed that organic fertilizer from water hyacinth has the potential to improve the household and community economy. This organic fertilizer can also help reduce the population of wild water hyacinth plants in Lake Toba. Processing methods for organic fertilizer from water hyacinth include picking, grinding, microdeck sowing, and decomposition. Implementation of this activity can provide benefits such as reducing the use of chemical fertilizers and increasing soil fertility. Liquid organic fertilizer from water hyacinth contains important nutrients such as nitrogen which can help plant growth. The use of organic fertilizer from water hyacinth can also contribute significantly to the length of plant cobs. In addition, composting water hyacinth can produce organic fertilizers that can be used by farmers as an alternative to chemical fertilizers. The use of water hyacinth as organic fertilizer has the potential to improve the economy of the people in the Lake Toba Region. However, this application also faces certain constraints and challenges. Therefore, policy recommendations and actions need to be taken to facilitate the sustainable use of water hyacinth organic fertilizer and contribute to improving the economy of the people in the Lake Toba Region